TEACHING SPEAKING ON LOCAL VACATION EXPERIENCE USING CUE CARDS - Yesi, Yesi; Ikhsanudin, Ikhsanudin; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to know whether or not there was a significant improvement on the eighth grade students? speaking achievement who were taught by using Cue Cards as a teaching medium. This research was carried out through pre-experimental design that consisted of one-group pre-test post-test. The sample of this research was the eighth grades students of SMP N 22 Pontianak. The number of students was 29. The technique of selecting the sample was cluster random sampling. The tool of collecting the data included oral test which was divided into two stages, pre-test and post-test. The score of pre-test and post-test were analyzed by using t-test and the effect size. The result of t-test was 3.568 and the effect size was 0.64. This indicates that the effect is moderate. The writer concludes that there is a significant effect of using Cue Cards in teaching speaking at the second year of SMP N 22 Pontianak. Keywords: Speaking, Cue Cards, Pre-experimental design.